Peranan Pendidikan Pelatihan (DIKLAT) Struktural Dan Teknis Dalam Meningkatkan Kompetensi Aparatur Cabang Dinas Pendidikan Siantar Provinsi Sumatera Utara - Triwandes Sinurat; Ridwin Purba (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The problem of this research is not optimal yet the employees of the branch of siantar education authorities north sumatera province presumably is still not optimal the technical of education and training that who have attended by employees so that it can influence toward competence of the apparatus branch of Siantar Education Authorities North Sumatera Province.The objective of this research is to get how much influence the technical of education and training toward the competence of the apparatus branch of Siantar Education Authorities north sumatera province and to get the new concept about technical education and training, and also the competence of employees.The methodology that used is qualitative method with the kind of Descriptive research. The population of this research is all the employees the branch of siantar education authrorities north sumatera province who have attended technical training in accordance with their field of work. The Analyzing of the data in this research is path analysis to explain the direct and indirect influence from each variable. The dependent variable in this research is variable of the technical education and training, and independent variable is the competence of employees. The result of this research is describing the technical education and training gave the significant influence toward the employees competence. The result of statistic calculation to show that the technical of education and training as simultaneous or partial effect toward apparatus of the branch of siantar education authorities north sumatera province and the other effect is not researched yet. Because of that, to improve apparatus competency need effective the technical education and training and accordance with work needed employees working. The finding of this research is to develop concept that the success of technical education and training by understanding, content, learning aids, practicable, feedback, interaction, and coordinated, when recruiting employees to attend technical training, it is carried out with a needs assessment system.